Adapting to a changing Colorado River : making future water deliveries more reliable through robust management strategies - Groves, David G.; Fischbach, Jordan R.; Bloom, Evan (Policy analyst); Knopman, Debra S.; Keefe, Ryan (RAND, 2013)
"The U.S. Bureau of Reclamation and water management agencies representing the seven Colorado River Basin States initiated the Colorado River Basin Study in January 2010 to evaluate the resiliency of the Colorado River system over the next 50 years and compare different options for ensuring successful management of the river's resources. RAND was asked to join this Basin Study Team in January 2012 to help develop an analytic approach to identify key vulnerabilities in managing the Colorado River basin over the coming decades and to evaluate different options that could reduce this vulnerability. Using a quantitative approach for planning under uncertainty called Robust Decision Making (RDM), the RAND team assisted the Basin Study by: identifying future vulnerable conditions that could lead to imbalances that could cause the basin to be unable to meet its water delivery objectives; developing a computer-based tool to define 'portfolios' of management options reflecting different strategies for reducing basin imbalances; evaluating these portfolios across thousands of future scenarios to determine how much they could improve basin outcomes; and analyzing the results from the system simulations to identify key tradeoffs among the portfolios. This report describes RAND's contribution to the Basin Study, focusing on the methodologies used to identify vulnerabilities for Upper Basin and Lower Basin water supply reliability and compare portfolios of options. The report provides a useful resource for other planners wishing to replicate or expand on the methodologies used for other studies"--Back cover